Formation of a Molecular Wire Using the Chemically Adsorbed Monomolecular Layer Having Pyrrolyl Groups - Kazufumi Ogawa; Norihisa Mino; Shin-ichi Yamamoto; Tadashi Ohtake (Journal of Nanotechnology)
A molecular wire containing polypyrrolyl conjugate bonds has been prepared by a chemical adsorption technique using 1,1,1-trichloro-12-pyrrolyl-1-siladodecane (PNN) and an electrooxidative polymerization technique, and the conductivity of the molecular wire without any dopant has been measured by using AFM/STM at room temperature. When sample dimension measured was about 0.3 nm (thickness of the conductive portion in the PNN monomolecular layer) ×100 μm (the average width of an electric path) ×2 mm (the distance between Pt positive electrode and the AFM tip covered with Au), the conductivity of the polymerized PNN molecular wire at room temperature was larger than 1.6 × 105 S/cm both in an atmosphere and in a vacuum chamber of 10−5 Torr. The activation energy obtained by Arrhenius' plots was almost zero in the temperature range between 320 and 450 K.